Data for "The Intrinsic Barrier Width and Its Role in Chemical Reactivity" - Qiu, Guanqi; Justus Liebig University Giessen (My University, 2023)
Raw IR spectra for the publication G. Qiu and P. R. Schreiner "The Intrinsic Barrier Width and its Role in Chemical Reactivity". File format is the Bruker vibrational spectroscopy software OPUS and MestReNova for visualization, processing, and analysis of IR data. The integrals of the relevant peaks were collected in the Excel file. Geometry optimizations and non-projected IRCs were computed at the MP2/cc-pVDZ level of theory using the Gaussian 16 package. All output files are provided. Tunneling half-lives and projected IRCs were determined at the CVT/SCT//MP2/cc-pVDZ level of theory using Polyrate Version 2017-c. Both the Polyrate code and the output files are provided.
Keywords: ddc:540